Analysis of Seawater Quality in Seaweed Farming Areas of Labuhan Kertasari Village, West Sumbawa Regency - Anang Fajrin; Abdul Rahman (Jurnal Pijar MIPA, 2026)
Seawater quality is a key factor determining the success of seaweed cultivation. Unsuitable water quality conditions can lead to reduced productivity or even the failure of seaweed cultivation. This study aims to analyze seawater quality at a seaweed cultivation site in Labuhan Kertasari Village, West Sumbawa Regency, to identify the factors causing cultivation failures that have occurred over the past year. Water quality is a critical factor influencing seaweed growth and productivity; therefore, a comprehensive evaluation of the water’s physical and chemical parameters is necessary. The research method used was quantitative descriptive, with sampling conducted at three horizontal points along a ±1 km stretch, each repeated three times. The parameters analyzed included temperature, salinity, dissolved oxygen (DO), pH, turbidity, current velocity, nitrate, and phosphate, measured in situ and through laboratory analysis. The results of the study indicate that most water quality parameters remain within the optimal range for seaweed cultivation, namely temperature 28–30°C, salinity 31–34 ppt, DO 4.2–6 mg/L, pH 6.4–8.2, turbidity 50–210 cm, current velocity 0.35–0.43 m/s, and phosphate at 0.03 mg/L, so that, in general, water conditions still support seaweed growth. However, nitrate levels were not detected at any sampling site, indicating low availability of nitrogen nutrients in the water. This suggests a potential nutrient limitation that could affect seaweed growth. Therefore, further analysis is needed regarding the role of nitrate nutrients in seaweed growth in Labuhan Kertasari Village. In addition, nutrient management strategies and regular water quality monitoring are needed to improve the success of seaweed aquaculture in the future.